Describing Translation Techniques Used in the Translation of Culturally Bound Terms in West Java Calendar of Event 2020 - Dyah Raina Purwaningsih; Nadia Gitya Yulianita (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This research aims at analyzing translation techniques used by the translator in translating the booklet "West Java Calendar of Event 2020" from Indonesian into English. This booklet is published by the Department of Tourism and Culture, West Java. Specifically, this research highlights the translation of culturally bound terms in the booklet. The researchers are interested in analyzing this topic because cultural-bound terms are considered challenging to translate; the translators must understand the cultural background of the languages they are translating. Moreover, it is not likely that translators can find one-to-one correspondence for each cultural term in the text. This study applies a descriptive qualitative method since the data are in the form of text and the researchers also play a role as the key instrument in collecting the data, in this case through document examination. In this research, total sampling technique is applied since the researchers take all of the culturally bound terms in the booklet. The research begins with collecting the cultural terms from the booklet, classifying them into cultural terms categories based on Newmark’s theory of cultural category, and determining the translation techniques based on Molina and Albir’s theory. The result shows that the translator mainly employs borrowing, amplification, description, and established equivalent techniques. There is a tendency that the translator prefers those techniques because it is hard for the translator to find one-to-one correspondence of the terms in the target language. Hopefully, this research will be beneficial for translators in deciding the proper translation techniques in translating cultural terms.